2020
DOI: 10.3390/antiox9020130
|View full text |Cite
|
Sign up to set email alerts
|

Healing Properties of Epidermal Growth Factor and Tocotrienol-Rich Fraction in Deep Partial-Thickness Experimental Burn Wounds

Abstract: Background: An experimental study was undertaken to determine the efficacy of the epidermal growth factor (EGF) with tocotrienol-rich fraction (TRF) cream in the wound-healing process on skin with deep partial-thickness burn in rats. Methods: A total of 180 Sprague-Dawley rats were randomly divided into six groups of six each and were: untreated control, treated with Silverdin® cream, base cream, base cream with c% EGF, base cream with 3% TRF or base cream with c% EGF and 3% TRF, respectively. Creams were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The primary goal of burn treatment is effective wound management, which largely determines the survival and prognosis of patients with severe burns [4,5]. Although the skin has the ability to heal itself, severe burns require a variety of interventions, such as healing drugs [6,7], debridement [8,9], and skin grafts [10,11]. However, for severe burns, skin grafts can cause harmful psychological effects [12] and severe disfigurement of the donor's skin [13].…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of burn treatment is effective wound management, which largely determines the survival and prognosis of patients with severe burns [4,5]. Although the skin has the ability to heal itself, severe burns require a variety of interventions, such as healing drugs [6,7], debridement [8,9], and skin grafts [10,11]. However, for severe burns, skin grafts can cause harmful psychological effects [12] and severe disfigurement of the donor's skin [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lowering of lipid peroxidation and nitrite levels were observed indicating reduced oxidative stress. TRF together with EGF presents a new therapeutic combination in the treatment of burn wounds 301 …”
Section: Tocotrienol Activity In Systemic Diseasementioning
confidence: 99%
“…Antioxidants, such as zinc and n-acetylcysteine, are used in COVID-19 patients to reduce inflammation [ 36 , 37 ]. Recent studies showed that several growth factors included in aaPRP, such as EGF [ 38 ] and IGF-1 [ 39 ], also have antioxidant effects. In addition, IGF-1 and hepatocyte growth factors were also known as antifibrogenic agents that help reduce inflammation-mediated fibrosis in the lungs of COVID-19 patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%